Acesso gratuito à justiça no processo civil brasileiro - Costa, Clerio Rodrigues da (2021)
The access of free justice is one of the rights that results from the constitutional guarantee of free legal, judicial and extrajudicial assistance, which is up to the State to provide. It's a right disciplined by the ―Código de Processo Civil‖ (articles 98 to 102), which resolves many issues that generated debate in doctrine and judicial processes. However, despite the praiseworthy concern of the legislator, it appears that this new Code does not resolve all the issues that the theme raises, in addition to creating others, which previously did not exist. In this work, without the claim to analyze all the existent problems, we try to point out some of them and suggest possible solutions. Here are some of these matters: a) The lack of legal provision of the review appeal against decisions that refuses to concede the right of free justice; b) The provision of the extinction of process, without considering its merit, if the author that have revoked the right of free justice don't realize the payment of the expenses that were discharged; c) The permanency of the service of free judiciary assistance administrated or coordinated by judicial authorities. d) The lack of express provision of dismissal of the payment for disadvantaged people of the fees in procedures of administrative usucaption, as a way of solving the controversy in a extrajudicially way